The Quality-Adjusted Cyclical Price of Labor - Bils, Mark; Kudlyak, Marianna; Lins, Paulo (Journal of Labor Economics, 2023)
We estimate cyclicality in labor’s user cost allowing for cyclical fluctuations in the quality of worker-firm matches and wages that are smoothed within employment matches. To do so, we exploit a match’s long-run wage to control for its quality. Using 1980–2019 National Longitudinal Survey of Youth data, we identify three channels by which recessions affect user cost: they lower the new-hire wage and wages going forward in the match, but they also result in higher subsequent separations. We find that labor’s user cost is highly procyclical, increasing by more than 4% for a 1 percentage point decline in unemployment.